Frequency domain analysis of triggered lightning return stroke luminosity velocity. Issue 4 (16th February 2017) - Carvalho, F. L.; Uman, M. A.; Jordan, D. M.; Moore, R. C.
Abstract: Fourier analysis is applied to time domain return stroke luminosity signals to calculate the phase and group velocities and the amplitude of the luminosity signals as a function of frequency measured between 4 m and 115 m during 12 triggered lightning strokes. We show that pairs of time domain luminosity signals measured at different heights can be interpreted as the input and the output of a system whose frequency domain transfer function can be determined from the measured time domain signals. From the frequency domain transfer function phase we find the phase and group velocities, and luminosity amplitude as a function of triggered lightning channel height and signal frequency ranging from 50 kHz to 300 kHz. We show that higher‐frequency luminosity components propagate faster than the lower frequency components and that higher‐frequency luminosity components attenuate more rapidly than lower frequency components. Finally, we calculate time domain return stroke velocities as a function of channel height using two time delay techniques: (1) measurement at the 20% amplitude level and (2) cross correlation. Key Points: Higher‐frequency luminosity components (300 kHz) propagate with faster phase velocity (80% faster) than lower frequency components (50 kHz) On average, frequency domain group velocities exceed phase velocities by approximately 44% Averaged over all heights, higher‐frequency luminosity components attenuate approximately 3 times faster than lower frequency components